The Role of Leadership, Partnership and Distribution on Business Performance of the Shrimp Paste Factory in Sidoarjo - Wanto, Hary; Utami, Desi (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
This research investigates the mediating role of distribution in the relationship between leadership, partnership, entrepreneurship, and business performance at shrimp paste factories in Sidoarjo. This research uses a quantitative approach using purposive sampling, namely distributing questionnaires to 60 shrimp paste distributor outlets that have collaborated with PT for at least 10 years. Gilang Jaya Raya. SmartPLS version 2.0.m3 facilitates data analysis. The research results show a direct positive influence of effective leadership on distribution practices, which emphasizes the importance of strong leadership for efficient distribution. Additionally, positive impacts were also seen on partnerships and entrepreneurship, highlighting their role in improving distribution channels. Importantly, this research reveals the significant positive influence of distribution on business performance, emphasizing the critical role of effective distribution strategies in overall business success. Although leadership has a direct impact on business performance, partnerships and entrepreneurship do not show a direct influence. However, the mediating role of distribution becomes clear, indicating that the positive influence of partnerships and entrepreneurship on business performance is realized through their impact on distribution practices. In conclusion, this research emphasizes the integral role of distribution as a mediator in forming the relationship between key factors and business performance in shrimp paste factories.